Factors that contribute to recurrence of schizophrenia in discharged clients attending to psychiatric clinic at Zomba mental hospital. - Malimba, Chikondi (Kamuzu University of Health Sciences, 2022)
The purpose of the study was to find out the factors that contribute to recurrence of schizophrenia in discharged clients attending to psychiatric clinic at Zomba mental hospital. The study was conducted at Zomba mental hospital, at out patient department to clients attending to psychiatric clinic. Health belief model was used as a theoretical basis for the study. A convenient sample of 30 subjects both male and female with a history of recurrence of schizophrenia was recruited in the study. A questionnaire which was translated into local language was used as a method for data correction and data was analysed manually. Data collection was done in 3 days. In brief the results indicated that drug non-compliance, non-attendance to psychiatric clinic for follow up care, lack of social network support, patient's lack of knowledge about the cause and the signs of relapse of their mental illness contributed to their recurrence of mental illness.